Influence of time on Zinc Oxide growth by hydrothermal method - Mohd Salim, Nurul Najwa (2020)
Zinc oxide (ZnO) structures were synthesized via hydrothermal method by the different times of growth from 20, 30, 40, 50 and 60 minutes. The effect of different growth time on crystallize size and optical properties of ZnO structures were studied and investigate. Then, the samples were characterized with X-ray diffraction (XRD) and Ultraviolet Visible (UV-Vis) spectroscopy. X-ray diffraction method revealed that ZnO structured exhibit the hexagonal zincite structure and the average crystallite size of ZnO particles was calculated. The average crystallite size of ZnO were 21.11, 21.13, 21.26, 21.38, and 21.49 nm for 20, 30, 40, 50 and 60 minutes respectively. The average crystallite size increasing with increasing the growth time. UV-Vis spectroscopy shows the absorption or reflectance of zinc oxide and the band gap was decrease throught the the growth time of ZnO. The direct energy band gap of ZnO structures were 3.22, 3.20, 3.10, 3.01 and 2.9 eV which are the energy band gap of the growth ZnO will be decrease with increasing the growth time. Thus, the growth time of the ZnO structures gave influence to the optical energy band gap properties, crystallite size and the structures of the ZnO.